The insider's guide to supervising government employees - Johnson, Kathryn M. (Management Concepts Press, 2011)
Effective supervisors are critical to the future of government. The knowledge, skills, and behaviors required to be an effective supervisor can come only through continuous learning and development.The Insider's Guide to Supervising Government Employees brings together the experiences of diverse supervisors from all aspects of government to offer a rich resource of lessons learned. Whether you are new to the supervisory role or a seasoned supervisor working to improve your and your staff's performance, this book is your practical, go-to guide.Starting with a seven-step, 38-item Supervisor Read.
Title from title screen
Keywords: Civil service -- Personnel management; Administrative agencies -- Personnel management; Employee-management relations in government; Supervision of employees; Government productivity; Fonction publique; Personnel; Direction; Administration publique; Personnel; Direction; Personnel; Supervision; Administration publique; Productivité; Administrative agencies; Personnel management; Civil service; Personnel management